Restoration of firearm serial numbers with electron backscatter diffraction (EBSD). (April 2015) - White, Ryan M.; Keller, Robert R.
Highlights: Serial number analogues are stamped in stainless steel and polished away. EBSD is used in the scanning electron microscope to view the sub-surface damage. The shape of the imprint is clearly restored using EBSD pattern quality maps. Abstract: Firearm serial numbers are a critical identifying mark, and restoration of destroyed serial numbers is often crucial for prosecution of a criminal case. A method is presented utilizing electron backscatter diffraction (EBSD) in the scanning electron microscope (SEM) which allows for clear visualization of die-stamped imprints which have been completely polished away. Evidence of the stamp can be observed to a depth of approximately 760 μm below the surface. With further development, the described method is capable of reconstructing an 8 character serial number in approximately 1 h.